Strategi Ritel Multisaluran dan Keputusan Pembelian Konsumen Produk Kecantikan: Pengalaman Sociolla - Wahyudi Wibowo (Faculty of Economics and Business, Jenderal Soedirman University, 2026)
This research analyses the effects of omnichannel experience on the repurchase intention of beauty products by employing customer satisfaction and trust as mediating variables. Data for this study were collected through online survey to 180 respondents in Indonesia. Results of the survey were analysed through the Structural Equation Modeling (SEM) techniques by the use of SmartPLS 3.0. Findings of the study confirm that omnichannel experience directly effects repurchase intention, customer satisfaction, and trust in the purchasing processes of beauty products. In addition, customer satisfaction and trust act as mediators in the relationship between customers’ omnichannel experiences and their repurchase intentions.